HUBUNGAN PENGETAHUAN IBU DENGAN PELAKSANAAN IMUNISASI BOSTER - Andalia Roza; Achmad Fichry (JOMIS (Journal of Midwifery Science), 2026)
Background: Booster immunization is an important effort to maintain children’s immunity against infectious diseases. However, booster coverage in several regions remains below the national target. One influencing factor is the mother’s knowledge regarding the importance of booster immunization.Methods: This study aimed to determine the relationship between maternal knowledge and booster immunization practices among mothers of toddlers. A cross-sectional quantitative design was used. The population included mothers with children aged 1–5 years visiting a community health center in Kuantan Singingi Regency. Sampling was conducted using a purposive sampling technique with 45 respondents. Data were collected using a structured and validated questionnaire. Data analysis was performed using the Chi-Square test with a significance level of 0.05.Results: The findings revealed that most respondents had good knowledge (60%) and high booster immunization implementation (66.7%). Statistical tests indicated no significant relationship between maternal knowledge and booster immunization practice (p = 0.254).Conclusion: The study concludes that maternal knowledge does not directly influence the implementation of booster immunization. Continuous education and motivation by healthcare workers are essential to improve mothers’ awareness and compliance with completing children’s immunizations.